Implementasi Program Roots Sebagai Upaya Pencegahan Bullying Melalui Agen Perubahan di Sekolah Menengah - Dita Hardiyanti; Yani Fitriyani; Ndaru Mukti Oktaviani; Muhammad Nurul Fajri (Jurnal Informasi Pengabdian Masyarakat, 2026)
This community service aims to identify forms of bullying and provide alternative solutions in the form of an anti-bullying roots program carried out at SMP Negeri 3 Klari, Karawang Regency, West Java. The methods used in this activity are carried out through a participatory approach. From the results of this community service, it is shown that bullying acts at SMP Negeri 3 Klari are quite common, with verbal bullying being the most common type that occurs at the school. One of the efforts made to reduce bullying is by implementing an anti-bullying roots program. Efforts made by using an anti-bullying program, putting up banners of forms of bullying, and anti-bullying declaration posters signed by all homeroom teachers and class leaders have proven to be quite effective in reducing the number of bullying acts at school. Agents of change as the main pillars of this program are very good at conveying positive messages to other students so that the campaign for SMP Negeri 3 Klari as a child-friendly school has yielded positive results.